2019
DOI: 10.1002/csr.1738
|View full text |Cite
|
Sign up to set email alerts
|

Reporting on sustainable development: A comparison of three Italian small and medium‐sized enterprises

Abstract: Nowadays, we are facing a new phase of capitalism. Information that is beyond financial capital and able to provide a more comprehensive picture of the path towards sustainable development of organizations is increasingly needed. A remarkable body of evidence already exists on how large listed companies are facing this change, but very little is known about small and medium-sized enterprises (SMEs). This work aims to analyse if and to what extent new forms of reporting such as sustainability and integrated rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 27 publications
2
66
1
Order By: Relevance
“…We also classified the studies we investigated by continent (Figure ). Most of the research studies we have found occur in Europe, which makes up 41% of the research (e.g., Girgenti, Peano, Baudino, & Tecco, ; Hertel & Menrad, ; Flynn & Davis, ; Jansson, Nilsson, Modig, & Hed Vall, ; Mayr, Mitter, & Aichmayr, ; Torkkeli, Kuivalainen, Saarenketo, & Puumalainen, ; Girella, Zambon, & Rossi, ), Asia accounts for 22% (e.g., Seth, Rehman, & Shrivastava, ; Singh, Olugu, & Musa, ) and South America at 19% (e.g., Lucato, Costa, & de Oliveira Neto, ; Pacheco, Caten, Jung, Navas, & Cruz‐Machado, ; Sarango‐Lalangui, Álvarez‐García, & del Río‐Rama, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also classified the studies we investigated by continent (Figure ). Most of the research studies we have found occur in Europe, which makes up 41% of the research (e.g., Girgenti, Peano, Baudino, & Tecco, ; Hertel & Menrad, ; Flynn & Davis, ; Jansson, Nilsson, Modig, & Hed Vall, ; Mayr, Mitter, & Aichmayr, ; Torkkeli, Kuivalainen, Saarenketo, & Puumalainen, ; Girella, Zambon, & Rossi, ), Asia accounts for 22% (e.g., Seth, Rehman, & Shrivastava, ; Singh, Olugu, & Musa, ) and South America at 19% (e.g., Lucato, Costa, & de Oliveira Neto, ; Pacheco, Caten, Jung, Navas, & Cruz‐Machado, ; Sarango‐Lalangui, Álvarez‐García, & del Río‐Rama, ).…”
Section: Resultsmentioning
confidence: 99%
“…We also classified the studies we investigated by continent ( Figure 4). Most of the research studies we have found occur in Europe, which makes up 41% of the research (e.g., Girgenti, Peano, Baudino, & Tecco, 2014;Hertel & Menrad, 2015;Flynn & Davis, 2016;Jansson, Nilsson, Modig, & Hed Vall, 2017;Mayr, Mitter, & Aichmayr, 2017;Torkkeli, Kuivalainen, Saarenketo, & Puumalainen, 2019;Girella, Zambon, & Rossi, 2019), Asia accounts for 22% (e.g., Seth, Rehman, & Shrivastava, 2018;Singh, Olugu, & Musa, 2016) and South America at 19% (e.g., Lucato, Costa, & ables on which SMEs can be categorized (Bar, 2015;Boiral, Ebrahimi, Kuyken, & Talbot, 2019;Groot et al, 2019;Long, Looijen, & Blok, 2018;Malesios et al, 2018;Prieto-Sandoval, Ormazabal, Jaca, & Viles, 2018). Our results show the pattern in the sectors that are studied from 2013 to 2019 (Figure 7).…”
Section: And Eco-friendly and Driversmentioning
confidence: 99%
“…The CSR strategy allows companies, in collaboration with their stakeholders (Martínez‐Ferrero, Suárez‐Fernández, & García‐Sánchez, ; Tolmie, Lehnert, & Zhao, ), to reconcile economic, social, and environmental aspects (Comisión Europea, ) thus allowing sustainable business behaviour (Cinquini, Passetti, Tenucci, & Frey, ; Engle, ; Girella, Zambon, & Rossi, ). Additionally, the adoption of informative practices enhances the reputation and image of companies (Bear, Rahman, & Post, ; Heikkurinen & Ketola, ; Hur, Kim, & Woo, ; Lii & Lee, ; Minor, ), allows access to new financial markets (Cheng, Ioannou, & Serafeim, ; García‐Sánchez, Hussain, Martínez‐Ferrero, & Ruiz‐Barbadillo, ; Jiraporn, Jiraporn, Boeprasert, & Chang, ), and creates a scenario of value and leadership for society (Cuadrado‐Ballesteros, García‐Sánchez, & Martínez Ferrero, ; Dhaliwal, Li, Tsang, & Yang, ; I. M. García‐Sánchez & Noguera‐Gámez, , ; Martínez‐Ferrero, Ruiz‐Cano, & García‐Sánchez, ; Stanaland, Lwin, & Murphy, ; Tata & Prasad, ).…”
Section: Introductionmentioning
confidence: 99%
“…The disclosure of non‐financial information (NFI) about business performance has become part of corporate communication policy within large companies. Conceptually, these reports should respond to the informative demands of the stakeholders, reporting in the most transparent way possible and reflecting relevant information on the social and environmental performance and impacts of the firms (Boiral, ; Girella, Zambon, & Rossi, ; Minutolo, Kristjanpoller, & Stakeley, ), which in turn could lead to greater responsibility for corporate actions (Cho et al, 2014; García‐Sánchez & Martínez‐Ferrero, ).…”
Section: Introductionmentioning
confidence: 99%